Zbiranje življenskih zgodb v slovenski etnologiji - Ramšak, Mojca (Etnolog. Nova vrsta (Ljubljana), 2000)
The article deals with the use of the (auto)biographical method in Slovene ethnology, focusing on authors who collect and analyse life stories in a manner which makes the contents of the stories the subject of the research, not just the research method. This means that the biographical material is treated as a primary source and that other literature has an auxiliary function. The approach reveals that there is no consistent line of development or systematic institutional collectimg and researching of life stories in Slovene ethnology with the exception of the already mentioned cases life stories are treated as a secondary and not as a primary source.
Keywords: ethnology; etnologija; Slovenci; Slovenes; biografska metoda; življenske zgodbe